The effects of climate change and fluctuations on the riparian bird communities of the arid Intermountain West. (26th October 2021) - Neate‐Clegg, M. H. C.; Horns, J. J.; Buchert, M.; Pope, T. L.; Norvell, R.; Parrish, J. R.; Howe, F.; Şekercioğlu, Ç. H.
Abstract: Riparian corridors are critical refuges for biodiversity in arid regions like the southwestern US. Birds in particular rely on these habitats for breeding and as migratory stopover sites within a resource‐scarce landscape. Climate change is likely to affect the distribution of resources across such landscapes and how birds use riparian zones. In this study, we used 15 years of bird‐banding data (1994–2008) from eight riparian sites across the state of Utah to examine the effects of variation in climate and vegetation on birds at the community and population level. We used generalized linear mixed models to analyze the effects of temperature, precipitation, El Niño Southern Oscillation (ENSO) and Normalized Difference Vegetation Index (NDVI) on daily total captures, species richness and community composition. We found that total captures and species richness increased in hotter, drier, less green years and in El Niño years, and the relationships were more pronounced for non‐riparian species than for species breeding in riparian zones. We also found changes in community composition in relation to temperature and precipitation. At the population level, we used capture–mark–recapture (CMR) models to analyze the effects of these covariates on the rates of population growth, recruitment and apparent survival. We found that population growth rates were negatively associated with temperature and ENSO for roughly half of the focal species. This pattern was almost entirely due to lower recruitment, likely caused by the combination of fewer resources and increased competition from the influx of non‐riparian birds into riparian oases. Our results have important implications for arid areas which are expected to become hotter and drier. Reducing other anthropogenic threats to riparian corridors, such as cattle grazing and water management, is likely to increase the resilience to climate change of riparian habitats and their avian residents. Abstract : Riparian corridors are vital to migratory birds in arid regions. Here, we show that in hotter, drier and less green years, more birds of more species are captured in riparian areas; however, the demographic rates of riparian breeding species decrease.